Enamel wet-process two-spraying and one-firing cover glaze material

By optimizing the component distribution ratio, the content of SiO2, B2O3, Al2O3 and other components is improved, and combined with the interaction of TiO2, Na2O, K2O, Na2SiF6 and other components, an enamel wet method two spray and one firing glaze glaze was developed to solve the problem of In the prior art, the problem of the surface glaze being easily exposed to the bottom and black is achieved, and efficient and low-cost production results are achieved.

CN119461848APending Publication Date: 2025-02-18ZHEJIANG KAIER NEW MATERIALS CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411650922.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-19
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The existing enamel wet spray and two firing surface glaze is easy to penetrate the bottom and reveal black during the wet spray and one firing process, which affects the quality of the porcelain surface, and has low production efficiency and high cost.

Method used

Develop an enamel wet method two spray and one firing glaze glaze. By optimizing the component distribution ratio, the content of SiO2, B2O3, Al2O3 and other components is increased, and combined with the interaction of TiO2, Na2O, K2O, Na2SiF6 and other components to enhance the turbidity of milk degree, leveling and color stability.

Benefits of technology

The surface glaze is achieved with high emulsion, not easy to penetrate the bottom and good leveling properties, which improves production efficiency, reduces costs, and ensures that the porcelain surface is smooth and delicate and has excellent texture.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005140896670000061
    Figure BDA0005140896670000061
  • Figure BDA0005140896670000071
    Figure BDA0005140896670000071
  • Figure BDA0005140896670000072
    Figure BDA0005140896670000072
Patent Text Reader

Abstract

The invention belongs to the technical field of glaze formula design, and provides an enamel wet process two-spraying and one-firing cover glaze material which is composed of the following compounds in percentage by mass: 29%-50% of SiO2, 10%-20% of B2O3, 3%-8% of Al2O3, 1%-5% of CaO, 15%-28% of TiO2, 1%-5% of P2O5, 8%-20% of Na2O, 3%-8% of K2O3, 0.5%-3% of MgO, 3%-8% of Na2SiF6 and 1%-4% of ZnO. The glaze formula has the advantages of being large in firing amplitude, stable in color, high in opalescence, high in whiteness, not prone to base penetration and black exposure, few in orange peel texture, smooth and fine in ceramic surface, excellent in texture and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of glaze formula design, and more particularly to a glaze for porcelain enamel using a wet two-spraying and one-firing surface glaze. Background Art

[0002] At present, there are basically two ways to prime almost all enamel products on the market. The first is the electrostatic dry method of two sprays and one firing. This method has high production efficiency, low labor intensity, and a relatively high degree of automation, but the material cost is expensive, some colors are easy to show through the bottom and black, and there is a lot of dust, which seriously affects the health of operators. The second method is the wet method of two sprays and two firings. The specific production method is to first spray the base glaze on the steel plate, fire and cool it, and then spray the top glaze and continue firing. This method requires two sprayings and two firings, and the firing temperature is high, which seriously affects the production efficiency and increases the production cost.

[0003] With the diversification of colors and shapes of decorative enamel plates, the current dry method of two-spraying and one-firing primer can no longer meet customer needs for some colors, and wet method primer must be used to produce the corresponding color effects. The wet method glazes on the market are basically wet method two-spraying and two-firing glazes. When wet method two-spraying and two-firing glazes are applied on wet method two-spraying and one-firing, orange peel texture is very serious, and it is easy to show the bottom and black, which seriously affects the quality of the porcelain surface.

[0004] In order to solve the above problems, it is a technical problem that technicians in this field need to urgently develop a wet two-spray one-fired glaze with high opacity, good leveling, and not easy to show through the bottom and reveal black. Summary of the invention

[0005] In order to solve the problems of high firing temperature, complex primer process, low production efficiency and easy bottom exposure and black exposure in existing porcelain glaze, the present invention provides a top glaze with simple primer process, high production efficiency and not easy to show the bottom and show black. The glaze formula has the advantages of large firing range, stable color, high opacity, high whiteness, not easy to show the bottom and show black, less orange peel texture, smooth and delicate porcelain surface, and excellent texture.

[0006] In order to achieve the above object, the present invention provides a enamel wet process two-spraying and one-firing glaze, which is composed of the following compounds in percentage by mass:

[0007] SiO229%~50%, B2O310%~20%, Al2O33%~8%, CaO 1%~5%, TiO215%~28%, P2O51%~5%, Na2O 8%~20%, K2O 3%~8%, MgO 0.5%~3%, Na2SiF63%~8%, ZnO 1%~4%.

[0008] Preferably, a enamel wet process two-spraying and one-firing glaze is composed of the following compounds in percentage by mass:

[0009] SiO229%~40%, B2O313%~19%, Al2O33%~5%, CaO 1%~3%, TiO215%~26%, P2O51%~2%, Na2O 8%~11%, K2O 4%~5%, MgO 1%~3%, Na2SiF63%~7%, ZnO1%~3%.

[0010] Preferably, a enamel wet process two-spraying and one-firing glaze is composed of the following compounds in percentage by mass:

[0011] SiO234.14%, B2O315.53%, Al2O33.53%, CaO 1.25%, TiO220.17%, P2O51.95%, Na2O 10.34%, K2O 4.18%, MgO 1.07%, Na2SiF66.72%, ZnO 1.12%.

[0012] Furthermore, the glaze is used after wet ball grinding.

[0013] The enamel wet process two-spray one-fired surface glaze provided by the present invention is a wet process glaze. The selected glaze needs to be mixed with water, clay, grinding additives, etc. in a certain proportion, ball-milled to a certain coarseness and fineness, and after obtaining the glaze slurry, it is sprayed on the wet process base glaze with a certain thickness, and then dried and fired according to a certain firing process.

[0014] The SiO2 in the glaze provided by the present invention is the main component of the glaze and the main glass network former. The higher the amount of SiO2 in the glaze, the higher the firing temperature. Increasing the content of SiO2 within a certain range can improve the mechanical strength and hardness of the glaze, and can also improve the chemical stability and thermal stability of the glaze.

[0015] The B2O3 in the glaze provided by the present invention is not only a solvent for the glaze but also a network former for the glaze, which promotes the formation of a glass phase at low temperatures. The increase in the B2O3 content increases the mechanical strength of the glaze and improves its abrasion resistance.

[0016] The Al2O3 in the glaze provided by the present invention is an intermediate oxide, which can be combined with not only silicon dioxide but also alkaline oxides, thereby improving the vitrification ability of the glaze and inhibiting crystallization, thereby significantly improving the elasticity, hardness and chemical stability of the glaze and improving the chemical corrosion resistance.

[0017] In the glaze provided by the invention, CaO is the main solvent in the glaze, which reduces the viscosity of the glaze melt, improves the fluidity of the glaze and the glossiness of the glaze surface, can reduce the expansion coefficient of the glaze, and improve the mechanical strength of the porcelain glaze.

[0018] The TiO2 in the glaze provided by the present invention increases the opacity, acid resistance and gloss of the glaze. Due to the good opacity, the glaze only needs to be coated with a thin layer, so the porcelain layer has high thermal stability and impact resistance and flexural strength.

[0019] The P2O5 in the glaze provided by the present invention can increase the opacification effect of the porcelain glaze, increase the reflectance coefficient of the porcelain layer, and cooperate with titanium dioxide to jointly improve the color stability of the glaze in the present invention.

[0020] The K2O and Na2O in the glaze provided by the present invention are strong fluxing agents of the glaze, which can significantly reduce the melting temperature and high-temperature viscosity of the glaze, increase the refractive index of the glaze, and thus improve the glossiness of the glaze surface.

[0021] The MgO in the glaze provided by the present invention is also a flux of the glaze, which can not only reduce the melt viscosity, but also reduce the expansion coefficient of the glaze and reduce the cracking of the glaze surface.

[0022] The Na2SiF6 in the glaze provided by the present invention is a strong co-solvent, which can significantly reduce the melting temperature of the glaze and the viscosity of the melt, and enhance the leveling property of the glaze. It is also a weak opacifier, which can promote the opacity of the porcelain glaze.

[0023] The ZnO in the glaze provided by the present invention can play a good fluxing role in a large range, reduce the expansion coefficient of the glaze, and improve the glossiness. However, excessive use will cause the glaze to crystallize and cause the glaze surface to lose its permeability.

[0024] It can be seen from the above technical solution that, compared with the prior art, the beneficial effects achieved by the present invention are:

[0025] (1) The present invention can effectively improve production efficiency, has high opacity, is not easy to show through the bottom and reveal black, has good leveling property and is a low-cost top glaze.

[0026] (2) The present invention uses the overall ratio of the above components, utilizes the strong opacity and high whitening property of TiO2, cooperates with the strong fluxing effect of Na2O and K2O, cooperates with the fluxing and enhanced leveling property of Na2SiF6, and then interacts with other components. The glaze of the present invention is used, and a wet two-spraying and one-firing process is adopted. The surface glaze of the present invention has good opacity, high whiteness, good leveling, is not easy to show the bottom and black, and the porcelain surface is smooth and delicate with good texture.

[0027] (3) TiO2 cooperates with other components to effectively increase the opacity and whiteness of the porcelain glaze, thereby ensuring that the top glaze can effectively cover the bottom glaze and prevent the bottom from showing through. DETAILED DESCRIPTION

[0028] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0029] Example 1

[0030] A wet-process two-spray-one-fired glaze comprising the following components: SiO2, B2O3, Al2O3, CaO, TiO2, P2O5, Na2O, K2O, MgO, Na2SiF6, ZnO, the specific mass fraction of each component is shown in Table 1; the glaze obtained in Example 1 is fired under the following three process conditions:

[0031] 820℃, calcination for 4min;

[0032] 840℃, calcined for 4min;

[0033] 860℃, sintering for 4min;

[0034] The enamel fired under the above process conditions was tested for L, a, b, and G values ​​using a colorimeter CD-6834 / 6836 produced by German BYK. The specific values ​​are shown in Table 2. The chromaticity values ​​obtained under the 840°C firing condition are recorded as L0, a0, and b0, respectively, and the chromaticity values ​​obtained under the 820°C and 860°C firing conditions are recorded as L0, a0, and b0, respectively. i 、a i 、b i , through the Hunter color difference formula:

[0035]

[0036] The color difference values ​​ΔE of the glaze in Example 1 at different firing temperatures were obtained and recorded in Table 2.

[0037] The test results of the thickness of the enamel porcelain layer obtained at different firing temperatures in Example 1, the presence of pinholes, whether the bottom is transparent and black, the severity of orange peel, acid resistance and alkali resistance are shown in Table 3.

[0038] The test methods and test results of acid resistance refer to GB / T 9989-2005, and those of alkali resistance refer to GB9988-1988.

[0039] Example 2

[0040] The main difference between this embodiment and embodiment 1 is that the mass fractions of the glaze components are different, and the specific differences are detailed in Table 1; the test results of various items at different firing temperatures in this embodiment are detailed in Tables 2 and 3.

[0041] Example 3

[0042] The main difference between this embodiment and embodiment 1 is that the mass fractions of the glaze components are different, and the specific differences are detailed in Table 1; the test results of various items at different firing temperatures in this embodiment are detailed in Tables 2 and 3.

[0043] Example 4

[0044] The main difference between this embodiment and embodiment 1 is that the mass fractions of the glaze components are different, and the specific differences are detailed in Table 1; the test results of various items at different firing temperatures in this embodiment are detailed in Tables 2 and 3.

[0045] Example 5

[0046] The main difference between this embodiment and embodiment 1 is that the mass fractions of the glaze components are different, and the specific differences are detailed in Table 1; the test results of various items at different firing temperatures in this embodiment are detailed in Tables 2 and 3.

[0047] Example 6

[0048] The main difference between this embodiment and embodiment 1 is that the mass fractions of the glaze components are different, and the specific differences are detailed in Table 1; the test results of various items at different firing temperatures in this embodiment are detailed in Tables 2 and 3.

[0049] Example 7

[0050] The main difference between this embodiment and embodiment 1 is that the mass fractions of the glaze components are different, and the specific differences are detailed in Table 1; the test results of various items at different firing temperatures in this embodiment are detailed in Tables 2 and 3.

[0051] Example 8

[0052] The main difference between this embodiment and embodiment 1 is that the mass fractions of the glaze components are different, and the specific differences are detailed in Table 1; the test results of various items at different firing temperatures in this embodiment are detailed in Tables 2 and 3.

[0053] Control group

[0054] The inventor purchased low-temperature wet-process enamel glaze from the market and fired it under the following three process conditions:

[0055] 820℃, calcination for 4min;

[0056] 840℃, calcined for 4min;

[0057] 860℃, sintering for 4min;

[0058] The enamel fired under the above process conditions was tested for L, a, b, and G values ​​using a colorimeter CD-6834 / 6836 produced by German BYK. The specific values ​​are shown in Table 2. The chromaticity values ​​obtained under the 840°C firing condition are recorded as L0, a0, and b0, respectively, and the chromaticity values ​​obtained under the 820°C and 860°C firing conditions are recorded as L0, a0, and b0, respectively. i 、a i 、b i , through the Hunter color difference formula:

[0059]

[0060] The color difference values ​​ΔE of the glaze in the control group at different firing temperatures were obtained and recorded in Table 2.

[0061] The test results of the enamel porcelain layer thickness obtained at different firing temperatures in the control group, the visual inspection of the presence of pinholes, whether the bottom is transparent and black, the severity of orange peel, acid resistance and alkali resistance are shown in Table 3.

[0062] The test methods and test results of acid resistance refer to GB / T 9989-2005, and those of alkali resistance refer to GB9988-1988.

[0063] Table 1 List of mass fractions of components in Examples 1 to 8 (%)

[0064] Components Example 1 Example 2 Example 3 Example 4 Example 5 Example 6 Example 7 Example 8 SiO2 34.14 29.31 39.31 34.14 32.67 34.14 34.14 34.14 B2O3 15.53 15.53 15.53 18.75 15.53 15.53 15.53 13.65 Al2O3 3.53 3.53 3.53 3.53 5 3.53 3.53 3.53 CaO 1.25 1.25 1.25 1.25 1.25 1.25 3 1.25 TiO2 20.17 26 15 20.17 20.17 20.17 20.17 20.17 P2O5 1.95 1.95 1.95 1.95 1.95 1.95 1.95 1.95 Na2O 10.34 10.34 10.34 10.34 10.34 8.41 8.59 10.34 K2O 4.18 4.18 4.18 4.18 4.18 4.18 4.18 4.18 MgO 1.07 1.07 1.07 1.07 1.07 3 1.07 1.07 Na2SiF6 6.72 6.72 6.72 3.5 6.72 6.72 6.72 6.72 ZnO 1.12 1.12 1.12 1.12 1.12 1.12 1.12 3

[0065] Table 2 Color values ​​and color difference values ​​of Examples 1 to 8 and the control group under different firing process conditions

[0066]

[0067]

[0068] Table 3 Surface quality of porcelain layer of Examples 1 to 8 and the control group under different process conditions

[0069]

[0070]

[0071] Combining Table 1, Table 2 and Table 3, it can be seen that by comparing Group 1 and Group 2, the thermal stability of the second group of samples decreased, and the L value became lower; by comparing Group 1 and Group 3, the L value of the third group of samples decreased significantly, and the turbidity became significantly worse; by comparing Group 1 and Group 4, the turbidity of the fourth group of samples decreased, and the orange peel pattern was obvious; by comparing Group 1 and Group 5, the porcelain surface of the fifth group of samples deteriorated; by comparing Group 1 and Group 6, the porcelain surface of the sixth group of samples was poor; by comparing Group 1 and Group 7, the porcelain surface of the seventh group of samples was rough; by comparing Group 1 and Group 8, the turbidity of the eighth group of samples decreased, and the stability was poor. In summary, in Examples 1 to 8, when the mass percentage of each component is different and the firing process is different, the porcelain surface quality of the enamel plate is relatively stable, the opacity is relatively high, the color stability is good, there are no pinholes, no obvious bottom exposure and black exposure, the orange peel wrinkles are relatively slight, and the acid and alkali resistance are good; compared with the control group, the commercially available wet-process glaze still has major problems in the wet-process two-spraying and one-firing process, and its opacity needs to be strengthened, the orange peel texture is relatively serious, and there is obvious bottom exposure and black exposure; among them, Example 1 has the best performance in all aspects among all formulas, and has excellent acid and alkali resistance tests, no bottom exposure and no black exposure, no pinholes, slight orange peel texture, and stable color under different firing processes.

[0072] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. A enamel wet process two-spray one-fired glaze, characterized in that: It is composed of the following compounds in percentage by mass: SiO229%~50%, B2O310%~20%, Al2O33%~8%, CaO 1%~5%, TiO215%~28%, P2O51%~5%, Na2O 8%~20%, K2O 3%~8%, MgO 0.5%~3%, Na2SiF63%~8%, ZnO 1%~4%.

2. The enamel wet process two-spraying and one-firing glaze material according to claim 1, characterized in that: It is composed of the following compounds in percentage by mass: SiO229%~40%, B2O313%~19%, Al2O33%~5%, CaO 1%~3%, TiO215%~26%, P2O51%~2%, Na2O 8%~11%, K2O 4%~5%, MgO 1%~3%, Na2SiF63%~7%, ZnO 1%~3%.

3. The enamel wet process two-spraying and one-firing glaze material according to claim 1, characterized in that: It is composed of the following compounds in percentage by mass: SiO234.14%, B2O315.53%, Al2O33.53%, CaO 1.25%, TiO20.17%, P2O51.95%, Na2O10.34%, K2O 4.18%, MgO 1.07%, Na2SiF66.72%, ZnO 1.12%.